Formation of thin film Cr-N composites under ion bombardment at low rates of chromium deposition - Guglya, A.; Litvinenko, M.; Marchenko, Y.; Vasilenko, R. (Вопросы атомной науки и техники, 2006)
One of peculiar features of the IBAD technology consists in that the damage level and concentration of implanted ions are distributed nonuniformly in the depth of deposited material. The calculations, we have done earlier [1], showed that the highest degree of nonequilibrium is realized in the first 50 nm of a coating. However, just in this thickness the nucleation and formation of the material structure is observed. The peculiarities of chromium coating formation without assisted irradiation and under bombarding with nitrogen ions having the energy of 30 keV were studied. The rates of chromium deposition were low, 0,05…0,1 nm/s. During the experiment the vacuum was maintained at a level of 4·10⁻³ Pa and was determined, in main, by the content of nitrogen molecules arriving from the discharging chamber of the ion source. The thickness within the range from 3 to 10 nm was investigated. The results have shown that at the earliest stages of the film growth solely chromium nitride CrN is formed. Sizes of visible nuclei are in the range from 1 to 4 nm, and their density is 1…3·10¹²cm⁻² . As the film thickness increases, the nuclei are growing, then their coalescence occurs and a uniform coating is formed. Chromium deposition without irradiation, but at the same nitrogen pressure, resulted in formation of chromium hcp structure with the following crystallographic parameters: a = 0,315 nm; c = 0,492 nm. The grain size was 3…4 nm. After reaching the coating continuity, the hcp structure was transformed into the bcc structure with the parameter a = 0,261 nm.